OPTIMALISASI FUNGSI SATUAN INTELIJEN DAN KEAMANAN KEPOLISIAN RESOR SOLOK SELATAN DALAM PENYELIDIKAN TINDAK PIDANA PERTAMBANGAN - Nasirwan, Nasirwan (UNES Journal of Swara Justisia, 2018)
The implementation of intelligence tasks within the Police is regulated in Article 39 of theRegulation of the Chief of Police of the Republic of Indonesia Number 23 of 2010. Thefunction of the Intelligence and Security Unit of Solok Selatan Police Resort has been tocarry out early detection and investigation of alleged mining crime. Seen from 2012 until2014 has been completed investigation followed up with the investigation of mining crime.The problem is optimizing the function of Satintelkam Polres Solok Selatan in theinvestigation of mining crime and obstacles encountered in the investigation. Specificationof this research is an analytical descriptive research with sociological juridical approach.The results show: first, optimization is done by conducting special and advancedintelligence education, conducting intelligence training in the field of mining crime, andestablish cooperation with related parties and communities. Both obstacles in theinvestigation of mining crime are lack of personnel capability and personnel behavior thatoften cooperate with the perpetrator as well as lack of supervision and control. Externally,the obstacles faced are most people are not providing information about the existence ofmining crime.